1990
DOI: 10.3177/jnsv.36.supplementii_s87
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Mechanisms Proposed to Explain the Hypocholesterolemic Effect of Soybean Protein versus Casein in Experimental Animals

Abstract: SummaryDiets containing soybean protein generally induce low levels of serum cholesterol in experimental animals, when compared with diets containing casein. The hypocholesterolemia in animals fed soybean protein is associated with increased rates of fecal excretion of bile acids and neutral steroids, low liver cholesterol concentra tions, increased numbers of hepatic apo B/E receptors, increased rates of hepatic cholesterol synthesis, increased rates of bile acid synthesis and decreased rates of lipoprotein c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 34 publications
1
24
0
1
Order By: Relevance
“…This is also in agreement with results reported on rats by Pant et al (1968) and Iauk et al (1989). Various effects on concentrations of insulin and glucagons (Beynen et al, 1990;Ham et al, 1993;Barath et al, 1990;Forsythe, 1986;Sanchez andHubbard, 1991 andScholz-Ahrens et al, 1990) have been reported due to feeding soy protein. Similar hormonal changes have been reported in rats after feeding velvet beans (Pant et al, 1968;Iauk et al, 1989).…”
Section: Serum Lipid Profilesupporting
confidence: 82%
“…This is also in agreement with results reported on rats by Pant et al (1968) and Iauk et al (1989). Various effects on concentrations of insulin and glucagons (Beynen et al, 1990;Ham et al, 1993;Barath et al, 1990;Forsythe, 1986;Sanchez andHubbard, 1991 andScholz-Ahrens et al, 1990) have been reported due to feeding soy protein. Similar hormonal changes have been reported in rats after feeding velvet beans (Pant et al, 1968;Iauk et al, 1989).…”
Section: Serum Lipid Profilesupporting
confidence: 82%
“…[1][2][3][4] These effects of soybean protein are estimated to be due partly to a reduction in cholesterol and triglyceride secretions from the liver to the blood circulation. 19) Thus dietary SPI can induce lipid-lowering activity through regulation of the hepatic contribution.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The hypocholesterolemic activity of soybean protein as compared with casein is known to be due to suppression of intestinal cholesterol absorption, 5,6) promotion of fecal steroid excretion, [7][8][9][10] increases in the cholesterol removal rate through the LDL receptor, 1,3,4) and so on. 11,12) Soybean protein has also been found to have triglyceride-lowering action.…”
mentioning
confidence: 99%
“…8,9) It is also assumed that SPI has cholesterol-lowering effects by stimulating cholesterol 7 -hydroxylase, the key enzyme converting cholesterol to bile acid. 10) On the other hand, DAG, which consists mainly of sn-1, 3 species, has been shown to suppress body fat accumulation in mice much more than dietary TG with a similar fatty acid composition, 11) and also to prevent increases in postprandial serum TG concentrations in healthy humans. 12) In addition, long-term intake of DAG also lowered the serum TG concentration in type II diabetic patients with hypertriglyceridemia.…”
mentioning
confidence: 99%